AKIBAT HUKUM PEMBATALAN PUTUSAN HOMOLOGASI BAGI DEBITUR DITINJAU DARI UNDANG-UNDANG KEPAILITAN DI INDONESIA - Yosefin, Kartika Sari (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2023)
When the bankruptcy decision is passed, at that time the debtor has lost his right to control and manage his assets. However, the Bankruptcy Law provides legal steps that can be taken by the debtor to regain control of his property, namely in the form of peace between the debtor and his creditors with a homologation decision. finally resulted in the settlement being requested to be canceled by the court (Cancellation of Homologation Decision), which resulted in bankruptcy being reopened and the debtor being declared again bankrupt.